Antioxidant and Radical Scavenging Effect of Blue-Green Alga Spirulina platensis - T Ramanathan, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Antioxidant and Radical Scavenging Effect of Blue-Green Alga Spirulina platensis